The Influence of Transcendental Communication on the Tahlilan Tradition at Nurul Huda Mosque Bandar Lampung - Khujaji, Afie Khotimil; Poyo, M. Denu; Waskito , Budhi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the influence of transcendental communication on the practice of the tahlilan tradition among the congregation of Nurul Huda Mosque in Bandar Lampung. Transcendental communication, defined as spiritual interaction between individuals and the divine, is seen as a key factor in shaping religious behavior and sustaining traditional religious rituals within the community. The research employs a quantitative approach using survey methods with 60 respondents selected through total sampling. Data were collected using a structured questionnaire that had passed validity and reliability tests, and analyzed using linear regression through IBM SPSS Statistics 25. The results indicate that transcendental communication significantly influences the tahlilan tradition, with a significance value of 0.004 (< 0.05) and a positive regression coefficient of 0.350. These findings suggest that the stronger the transcendental communication experienced by individuals, the greater their belief in and participation in the tahlilan tradition. Furthermore, the study confirms that the research data meet the classical assumptions of normality and homoscedasticity. In conclusion, transcendental communication plays a substantial role in reinforcing collective religious traditions and spiritual continuity within local Muslim communities. This research contributes to a broader understanding of how spiritual dimensions influence the preservation of Islamic cultural-religious practices in a contemporary setting.